2022
DOI: 10.1371/journal.pone.0272623
|View full text |Cite
|
Sign up to set email alerts
|

Differential progression of unhealthy diet-induced hepatocellular carcinoma in obese and non-obese mice

Abstract: Background Non-alcoholic fatty liver disease (NAFLD) ranks first among liver diseases in Western countries. NAFLD is typically associated with obesity and diabetes, however it also develops in lean individuals without metabolic syndrome. The prevalence of lean NAFLD is 7 percent in the U.S. and 25–30 percent in some Asian countries. NAFLD starts with excess liver fat accumulation (NAFL), progresses to nonalcoholic steatohepatitis (NASH), cirrhosis and hepatocellular carcinoma (HCC). The pathogenesis of lean NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…The increased number of DMRs and hypermethylation in the obese mice may be driven by dietary choline, which is involved in one-carbon metabolism in methylation [39]. Additionally, our previous work found that mice with HCC in the context of obesity had higher plasma fasting glucose and cholesterol levels than lean mice with HCC [40]; differences in glucose levels may contribute to the differential methylation patterns identified, which is in line with previous work that found glucose levels were associated with CpG methylation levels [41].…”
Section: Discussionmentioning
confidence: 97%
“…The increased number of DMRs and hypermethylation in the obese mice may be driven by dietary choline, which is involved in one-carbon metabolism in methylation [39]. Additionally, our previous work found that mice with HCC in the context of obesity had higher plasma fasting glucose and cholesterol levels than lean mice with HCC [40]; differences in glucose levels may contribute to the differential methylation patterns identified, which is in line with previous work that found glucose levels were associated with CpG methylation levels [41].…”
Section: Discussionmentioning
confidence: 97%
“…High-fat, high-glucose, and low-fiber Western diets are known to accelerate progression from MASH to MASH-HCC [40]. In addition, the Western diet increases the abundance of the genus Fusobacterium and decreases the abundance of the genus Roseburia in the intestine [41].…”
Section: Discussionmentioning
confidence: 99%
“…At the endpoint (64 weeks of age), Hymel et al. 171 observed that tumor progression was faster in males. None of the female lean mice fed a CD-HFFC diet developed HCC (only dysplastic nodules were reported), while 50% of female obese mice fed a CS-HFFC diet developed HCC at the endpoint.…”
Section: Sex-based In Vivo Models Of Hepatocellula...mentioning
confidence: 99%
“… Hymel et al. 171 Hepatocyte-specific Pten-deficient mice (C57BL/6J background) at 40 weeks and 76 weeks Lower HCC incidence and smaller HCC size in females. Anezaki et al.…”
Section: Sex-based In Vivo Models Of Hepatocellula...mentioning
confidence: 99%